1992
DOI: 10.1115/1.2906580
|View full text |Cite
|
Sign up to set email alerts
|

Coating Effect on Particle Trajectories and Turbine Blade Erosion

Abstract: Gas turbine engines operating in dusty environments are exposed to erosion and performance deterioration. In order to improve the erosion resistance, nickel and cobalt superalloy blades and vanes are widely used in the hot section of gas turbines. Protective coatings have been used to enhance superalloy resistance to hot erosion. An investigation has been conducted to study coal ash particle dynamics and resulting blade erosion for both uncoated and coated blades of a two-stage axial flow gas turbine. A quasi-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…A study on sand ingestion in an axial fan by Ghenaiet et al [6] indicated that after a 6 hour sand ingestion test, there was a 7% reduction in adiabatic efficiency. This paper provides a methodology and test results conducted on a simple test coupon representative of an airfoil leading edge, which is one of the most difficult areas to cool and one of the most susceptible areas to sand blockage as shown in studies on external deposition tests by Tabakoff et al [7] and Kim et al [2]. The test coupon contains an array of film-cooling holes with a typical diameter and orientation as seen in a leading edge of a turbine vane.…”
Section: Gt2006-90067mentioning
confidence: 99%
“…A study on sand ingestion in an axial fan by Ghenaiet et al [6] indicated that after a 6 hour sand ingestion test, there was a 7% reduction in adiabatic efficiency. This paper provides a methodology and test results conducted on a simple test coupon representative of an airfoil leading edge, which is one of the most difficult areas to cool and one of the most susceptible areas to sand blockage as shown in studies on external deposition tests by Tabakoff et al [7] and Kim et al [2]. The test coupon contains an array of film-cooling holes with a typical diameter and orientation as seen in a leading edge of a turbine vane.…”
Section: Gt2006-90067mentioning
confidence: 99%
“…Such situations arise in various industries such as the oil and gas production industry, aeronautical, power station, etc. [2][3][4][5][6][7][8][9][10][11]. It has been estimated that in power stations, solid particle erosion costs American utilities over $150 million annually due to reduction of efficiency, heat loss and maintenance and repair costs [12].…”
Section: Background and Motivationmentioning
confidence: 99%
“…0~4 、 0~4 are all experimental constants related to the material propertites of the particle and solid surface. In this work, those constants are adopted according to Table 1 recommended by Tabakoff and Metwally(1992). Table 1 Particle rebounding constants…”
Section: Reflecting Mechnismmentioning
confidence: 99%